IMPLICATIONS OF CONSTRUCTIVISM LEARNING THEORY ON STUDENTS' CRITICAL THINKING SKILLS: A THEORETICAL STUDY - Hidayatullah, Umar Hasan (Abjadia : International Journal of Education, 2024)
Education is an important foundation in the development of individuals and society. In the challenging modern era, the education system must be able to develop critical thinking skills in students. Constructivism learning theory, which emphasizes students' active role in constructing knowledge, offers a relevant approach for this purpose. This study explores the implications of applying constructivism theory to the development of student's critical thinking skills through a qualitative method with theoretical review and literature study. The findings show that problem-based learning strategies, group discussions, and collaborative projects are effective in improving critical thinking skills. However, the implementation of this theory varies depending on the educational context and teacher readiness. In developed countries, the implementation of constructivism is more successful than in developing countries, which face challenges such as lack of resources and teacher training. The results of this study offer practical guidance for educators and policymakers in designing curricula that are responsive to student's needs, as well as making a significant contribution to the education literature.